A new system call classification for android mobile malware surveillance exploitation via SMS message - Mohd Saudi M.; Abd Rahman M.Z.; Mahmud A.A.; Basir N.; Yusoff Y.S. (Springer Verlag, 2024)
Indexed by Scopus